2021
DOI: 10.1124/jpet.121.000712
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin Conjugates in Tissue Regeneration 1 Promote Alveolar Fluid Clearance by Activating Alveolar Epithelial Sodium Channels and Na, K-ATPase in Lipopolysaccharide-Induced Acute Lung Injury

Abstract: Acute respiratory distress syndrome (ARDS), a common and fatal clinical condition, is characterized by the destruction of epithelium and augmented permeability of the alveolar-capillary barrier. Resolvin conjugates in tissue regeneration (RCTR1) is an endogenous lipid mediator derived from DHA, exerting pro-resolution effects in the process of inflammation. In our research, we evaluated the role of RCTR1 in alveolar fluid clearance (AFC) in Lipopolysaccharide-induced ARDS/ALI rat model. Rats were injected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…It appears that in severe lung injury other mediators such as NO, proteases, and oxidants involved in different signaling pathways may also participate along with alveolar epithelial cell injury [ 7 ]. Recent reports showing the resolution of lung edema and injury in-vivo and in-vitro through ALX/cAMP/PI3K/Nedd4-2 and WNK4/SPAK axis [ 47 , 48 ] support this argument. For example, Resolvin conjugates in tissue regeneration 1 (RCTR1), a series of docosahexaenoic acid–derived lipid mediators which can be released from macrophages when externally applied to LPS induced lung injury model upregulates ENaC abundance and improves alveolar fluid clearance [ 47 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It appears that in severe lung injury other mediators such as NO, proteases, and oxidants involved in different signaling pathways may also participate along with alveolar epithelial cell injury [ 7 ]. Recent reports showing the resolution of lung edema and injury in-vivo and in-vitro through ALX/cAMP/PI3K/Nedd4-2 and WNK4/SPAK axis [ 47 , 48 ] support this argument. For example, Resolvin conjugates in tissue regeneration 1 (RCTR1), a series of docosahexaenoic acid–derived lipid mediators which can be released from macrophages when externally applied to LPS induced lung injury model upregulates ENaC abundance and improves alveolar fluid clearance [ 47 ].…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports showing the resolution of lung edema and injury in-vivo and in-vitro through ALX/cAMP/PI3K/Nedd4-2 and WNK4/SPAK axis [ 47 , 48 ] support this argument. For example, Resolvin conjugates in tissue regeneration 1 (RCTR1), a series of docosahexaenoic acid–derived lipid mediators which can be released from macrophages when externally applied to LPS induced lung injury model upregulates ENaC abundance and improves alveolar fluid clearance [ 47 ]. Mesenchymal stem cells secrete a wide range of cytokines, growth factors, and microRNAs [ 49 ] attenuating edematous lung injury via enhancing γ-ENaC expression, through activating PI3K/AKT signaling [ 36 ].…”
Section: Discussionmentioning
confidence: 97%
“…Recently, for example, Ma et al demonstrated that PCTR1 inhibits macrophage pyroptosis, attenuates lung damage, and improves mouse survival in LPS‐induced sepsis 50 . In addition, RCTR1 accelerates the rate of alveolar fluid clearance and promotes the resolution of inflammation in acute lung injury 51 . Thus, it is likely that the 4S,5R‐RCTR1 will also demonstrate potent protective actions across diverse disease models.…”
Section: Discussionmentioning
confidence: 99%
“…50 In addition, RCTR1 accelerates the rate of alveolar fluid clearance and promotes the resolution of inflammation in acute lung injury. 51 Thus, it is likely that the 4S,5R-RCTR1 will also demonstrate potent protective actions across diverse disease models. SPMs are biosynthesized from omega-3 essential PUFAs, primarily docosahexaenoic acid (DHA) and EPA, in the presence of active enzymes including lipoxygenases, hydrolases, and GSTs that produce and act on specific epoxide-containing intermediates.…”
Section: Synthetic 4s5r-rctr1 Increases Erythrophagocytosis Of Senesc...mentioning
confidence: 99%
“…Moreover, the important role of the macrophage-derived specialized pro-resolving mediators (SPMs) in promoting AFC during ARDS has been gradually recognized [ 284 ]. For example, the resolvin conjugates in tissue regeneration 1 [ 285 ] as well as the maresin conjugates in tissue regeneration 1 [ 204 ] belong to SPMs, which have been recently implicated to upregulate ENaC and Na,K-ATPase by activating the cAMP/PI3K/AKT signaling pathways, and results in alleviating pulmonary edema in preclinical ARDS models. However, there is a lack of significant clinical studies of either administered exogenously or induction of endogenous SPMs in ARDS patients.…”
Section: Emerging Pharmacologic Therapies For Ardsmentioning
confidence: 99%